A survey of acceptor dopants for β-Ga2O3 - Lyons, John L (Semiconductor science and technology, 2018)
With a wide band gap, high critical breakdown voltage and commercially available substrates, Ga2O3 is a promising material for next-generation power electronics. Like most wide-band-gap semiconductors, obtaining better control over its electrical conductivity is critically important, but has proven difficult to achieve. Although efficient p-type doping in Ga2O3 is not expected, since theory and experiment indicate the self-trapping of holes, the full development of this material will require a better understanding of acceptor dopants. Here the properties of group 2, group 5 and group 12 acceptor impurities in β-Ga2O3 are explored using hybrid density functional calculations. All impurities are found to exhibit acceptor transition levels above 1.3 eV. After examining formation energies as a function of chemical potential, Mg (followed closely by Be) is determined to be the most stable acceptor species.